Penatalaksanaan Fisioterapi Pada Kasus Piriformis Syndrome Sinistra Di RSUD Bantul - Septaningrum, Yolanda Sonya, Isnaini Herawati S.St. FT, M.Sc (2016)
Background : Approximately 15% of the population of sciatica (ischialgia) is the piriformis syndrome that occurs due to sciatica nerve (nerve ischiadicus) compressed or irritated by the piriformis muscle shortening causing experiencing pain, tingling in the buttocks area until the sciatica nerve travels. Objective : To determine the benefits of short wave diathermy, electrical transcutaneus nerve stimulation (TENS) and exercise therapy on pain reduction, increase muscle strength, and improve functional ability in the case of the left piriformis syndrome. Methods : Giving short wave diathermy, electrical transcutaneus nerve stimulation (TENS) and exercise therapy in the from of active resisted exercise, active exercise, and passive stretching exercise. Result :After treatment, the result obtained T1-T6 is pain reduction assessed by Verbal Descriptive Scale (VDS), followed by an increase in muscle strength assessed with Manual Muscle Testing (MMT) wich can lead to improved functional ability assessed by Owestry Low Back Pain Indeks. Conclusions : Provision of physiotherapy intervention against the form of SWD, TENS, and exercise therapy showed a reduction of pain, increased muscle strength and improved functional ability.